WAYS TO IMPROVE OPEN MARKET POLICY BASED ON FOREIGN EXPERIENCE - Murodova Mohigul Chori qizi (Journal of Artificial Intelligence and Digital Economy, 2024)
In the article, the current problems related to the introduction of the foreign experience of the open market lever in the monetary policy of the Republic of Uzbekistan are identified and scientific proposals aimed at solving them are developed